The Reversal of Fortune, Extractive Institution and the Historical Roots of Racism - Matthew Bonick; Antonio Farfan-Vallespin (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We show differences in levels of racism within a sample of former European colonies can be traced to historical institutions. Our identification strategy relies on the reversal of fortune, a historical shock capturing the exogenous establishment of different institutions during the onset of European colonization. Using both OLS and multilevel analysis, we find, extractive historical institutions to be a strong predictor of higher levels of racism independent of present and other explanatory factors at the individual and country levels. We argue and provide evidence this relationship is causal and operates through internal norms, beliefs and values.
Keywords: J15; N30; N40; Z10; 330